(untitled) (Modern education and development, 2025)
This article explores whether knowing multiple languages should be considered an intellectual advantage or a social necessity. Through a review of existing literature and theoretical analysis, the study examines cognitive benefits associated with multilingualism, such as enhanced memory, attention, and problem-solving skills. It also discusses the practical importance of multilingualism in today’s globalized world, highlighting its role in social integration, career opportunities, and effective communication. The findings suggest that multilingualism serves both as a means of intellectual growth and a critical social skill, emphasizing the intertwined nature of cognitive and societal factors in language acquisition.